Untargeted Metabolic Fingerprinting Reveals Impact of Growth Stage and Location on Composition of Sea Buckthorn (Hippophaë Rhamnoides) Leaves - Raghunath Pariyani; Maaria Kortesniemi; Jaana Liimatainen; Jari Sinkkonen; Baoru Yang (Wiley, 2022)
Sea buckthorn (Hippophaë rhamnoides) is increasingly cultivated to produce raw materials for food and nutraceuticals. There is little knowledge on composition of sea buckthorn leaves (SBLs) and the key factors influencing the composition. This research aims to unravel the metabolic profile of SBLs and the effects of cultivar, location and stage of growth, and climatic conditions on the metabolic profile of SBLs. Leaves of two sea buckthorn cultivars grown in the south and north of Finland during two consecutive growth seasons were studied using untargeted nuclear magnetic resonance (NMR) metabolomics. The highest variance in the metabolic profile was linked to the growth stage, wherein leaves from the first 7 weeks of harvest were characterized with higher abundance of polyphenols, while relatively higher abundance of carbohydrates and sugars was observed in the later weeks. The growth location attributed for the second highest variation, wherein the north–south comparison identified fatty acids and sugars as discriminatory metabolites, and the potential association of metabolome to natural abiotic stressors was revealed. An inverse correlation between carbohydrate/sugar content as well as fatty acids of higher carbon chain length with the temperature variables was evident. The supervised chemometric models with high sensitivity and specificity classified and predicted the samples based on growth stage and location, and cultivar. Nontargeted NMR-metabolomics revealed the metabolic profile of SBLs and their variation associated with various biotic and abiotic factors. Cultivar and growth stage are key factors to consider when harvesting SBLs for use in food and nutraceuticals.
Practical Application
Globally, sea buckthorn cultivation has been rapidly increasing due to the known health-promoting benefits of the berries and leaves of the plant. The current research obtained new comprehensive information on the compositional profile of sea buckthorn leaves as well as the impact of major contributory factors, such as cultivars, the advancement of growth stage, geographical location, and weather parameters. The findings of this research provide new knowledge and guidance for plant breeding, cultivation and commercial utilization of sea buckthorn leaves as raw materials for food, feed, and nutraceuticals.